PENDIDIKAN KAUM TERTINGGAL DI SAMPANG - Ardhie Raditya (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2017)
As stated in Perpres number 131/2015, Sampang is one of the least developed regions in Indonesia. This lag phenomenon is seen by the educational aspect. This phenomenon can be seen in SDN Bluuran 2 Sampang which appears in several ways: First, the students and their parents have no hope and ideal future. Their goals goes to school is without hope. Second, the success of education is not determined by factors cleverness, but luckiness. Third, the strong geographical and religious pressures force the surrounding communities to have no freedom to determine their educational future